Madrasah Nizamiyah sebagai Instrumen Politik Pendidikan Dinasti Saljuk dalam Konsolidasi Ortodoksi Sunni - Afif, Muhammad Sholeh; Padil, Moh; Zuhroh, Ni'matuz (TSAQOFAH, 2026)
Although the relationship between education and power has received attention in various previous studies, studies that specifically discuss Madrasah Nizamiyah as a systematic instrument of state religious consolidation through critical sociological analysis remain limited. This study aimed to analyze the role of Madrasah Nizamiyah as an educational-political instrument of the Seljuk Dynasty in consolidating Sunni orthodoxy and building political legitimacy. This study used a qualitative-interpretive approach with a historical-sociological design. Textual data sources were selected deliberately through purposive sampling, including primary works such as Siyasatnama by Nizam al-Mulk and Al-Kamil fi al-Tarikh by Ibn al-Athir. Data were collected through documentation study and were then analyzed using content analysis and contextual analysis with the theoretical frameworks of Weber’s legitimacy theory and Bourdieu’s cultural capital. The results showed that the Madrasah Nizamiyah network functioned as a “bureaucratic factory” that effectively converted political capital into symbolic-religious authority through curriculum standardization, a sustainable waqf funding system, and the strategic recruitment of influential ulama such as al-Ghazali. These findings contribute to the development of studies on the sociology of Islamic education and expand understanding of the relationship between religion and the state in medieval Islamic civilization. The conclusion of this study confirms that the institutionalization of education played a crucial role in maintaining social stability and state hegemony. The implications of this study include theoretical contributions to the literature on social reproduction as well as practical recommendations for strengthening the independence of religious educational institutions through financial autonomy and curriculum integration in facing modern ideological challenges.